Energy storage medium and preparation method and application thereof
By using energy storage medium composed of composite capsules in the drilling fluid for heat exchange, the problem of rising temperature of high-temperature underground drilling fluid is solved, efficient drilling fluid cooling is achieved, and drilling costs and accident risks are reduced.
Patent Information
- Application Number
- CN202311097925.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
AI Technical Summary
During high-temperature downhole drilling, drilling fluid and drilling tools fail due to long-term exposure to high temperature conditions, resulting in increased drilling fluid temperature, affecting drilling efficiency and safety. The existing cooling methods are inefficient and large in size and have a long cycle time.
An energy storage medium is used, which consists of a composite capsule, which includes an outer layer of carboxymethyl chitosan and an inner layer of emulsified paraffin. It uses a heat exchange medium (usually water) to exchange heat with the heat exchange medium after heating in the on-site circulating cooling pipeline of the drilling fluid. The cladding effect of carboxymethyl chitosan is used to restore the crystal state of the inner core of the microsphere to achieve rapid cooling.
This method can significantly improve the cooling efficiency of drilling fluid, and can improve the cooling efficiency by at least 50% compared to water cooling, reducing the risk of complex underground accidents and reducing drilling costs.
Abstract
Description
Technical Field
[0001] The invention relates to the field of phase change energy storage materials, and in particular to an energy storage medium and a preparation method and application thereof. Background Art
[0002] At present, as the exploration and development of oil and gas goes deeper and deeper, the temperature of the drilled formation is getting higher and higher. Under the long-term high temperature conditions at the bottom of the well, the downhole fluid and the drill bit combination will suffer fatigue failure to varying degrees. In particular, for expensive precision instruments such as rotary guides, their electronic components will be damaged to varying degrees, resulting in failure of the entire instrument. Drilling has to be stopped, the drill has to be pulled out, and the drill bit has to be replaced. On the one hand, this may lead to increased replacement costs. On the other hand, during the process of stopping drilling, it may induce complex accidents such as well wall collapse and drill stuck, which will lead to an increase in the time for complex downhole processing. In severe cases, it may cause the entire wellbore to be scrapped, resulting in serious economic losses.
[0003] To this end, oil exploration and development engineers use different methods to reduce drilling fluid circulation. One is downhole cooling. By adding low-temperature fluid or a certain amount of energy storage material to the downhole fluid, the downhole drilling fluid temperature can be partially reduced. However, this method requires the addition of more fluid or energy storage material, which may have a greater impact on the flow performance of the drilling fluid. Another method is ground cooling, which uses cooling water circulation and air heat exchange cooling on the ground to cool down. However, due to the low heat storage efficiency of water, its cooling effect is poor. If the temperature is reduced by extending the pipeline, it may cause the device to be too large, the circulation time to be too long, and the ability to recirculate into the bottom of the well is weakened. Therefore, it is more realistic to find a more effective energy storage fluid in the ground cooling circulation system. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the first aspect of the present invention provides an energy storage medium, wherein the energy storage medium has the following component contents calculated by mass percentage: 33%-46% composite capsule, 0.3%-0.9% viscosity enhancer and the balance of deionized water. The composite capsule comprises carboxymethyl chitosan in the outer layer and emulsified paraffin emulsified by polyacrylamide in the inner layer, and the following component contents calculated by mass percentage: the composite capsule comprises 50%-70% of carboxymethyl chitosan and 30%-50% of emulsified paraffin. The energy storage medium described in the present invention is obtained by coating carboxymethyl chitosan on the outside of emulsified paraffin through emulsified paraffin modified by polyacrylamide, and utilizing the mutual mixing effect of carboxymethyl and amide groups to restore the internal crystal state of the microsphere core material in the energy storage medium coated with carboxymethyl chitosan. When in use, a heat exchange medium, usually water, is directly pumped into a circulating cooling pipeline at the drilling fluid site, and the circulating cooling pipeline contacts the outer wall of the pipeline where the drilling fluid is located for heat exchange, and the circulating cooling pipeline where the heated heat exchange medium is located is contacted and connected with the pipeline where the energy storage medium is located. At this time, the energy storage medium and the heated heat exchange medium are continuously heat exchanged and circulated and then cooled, so as to achieve the purpose of quickly reducing the temperature of the drilling fluid.
[0005] Furthermore, the thickener includes at least one of polyacrylamide, hydroxymethyl cellulose and carboxymethyl starch. The thickener mainly functions to improve the suspension of the capsule. If the suspension energy is insufficient, the capsule will settle, which may cause certain blockage or unstable pump pressure during circulation.
[0006] Furthermore, the molecular weight of the polyacrylamide is 5.0×10 6 -1.0×10 7 .
[0007] Furthermore, the etherification degree of the hydroxymethyl cellulose is 1.0.
[0008] Furthermore, the degree of substitution of the carboxymethyl starch is 0.6.
[0009] Furthermore, considering the fluidity of the fluid in the pipeline, in order to ensure that the energy storage medium can flow better in the pipeline, the particle size of the composite capsule is 2.0-4.0 mm, and based on the balance between shear failure and maximum paraffin embedding rate, the outer wall thickness of the composite capsule is 1.0-2.0 mm.
[0010] Furthermore, the phase change temperature of the energy storage medium is 14-21° C., and the cooling efficiency is 18.5%-25.4%.
[0011] In a second aspect, the present invention provides a method for preparing the composite capsule, comprising the following steps:
[0012] S11, adding carboxymethyl chitosan into deionized water, stirring and dispersing the mixture evenly to obtain a first mixed solution;
[0013] S12, adding emulsified paraffin to the first mixed solution, stirring to complete the reaction, and then vibrating, sieving, rinsing and drying to obtain composite capsules.
[0014] The carboxymethyl chitosan is obtained by reacting chloroacetic acid with chitosan under NaOH conditions, and is preferably C6-O-carboxymethyl substituted, with a substitution degree DS = 0.9. The particle size of the obtained composite capsule is 2.0 mm to 4.0 mm, and the wall thickness is 1.0 mm to 2.0 mm.
[0015] Furthermore, in step S11, after adding deionized water into the closed autoclave, the system temperature is set to 60-80°C.
[0016] Furthermore, in step S11, carboxymethyl chitosan is added within 30 to 60 minutes.
[0017] Furthermore, in step S11, the stirring speed is 1000-3000 rpm, and the stirring time is 60-90 min.
[0018] Furthermore, in step S12, the emulsified paraffin is added within 20 to 30 minutes, and stirring is continued for 60 to 90 minutes after the addition.
[0019] Furthermore, the mesh size of the oscillation sieve is 20 meshes.
[0020] Furthermore, the drying temperature is 60° C. and the drying time is 48 h.
[0021] Furthermore, the preparation method of the emulsified paraffin comprises:
[0022] S21, adding low molecular weight polyacrylamide into deionized water, stirring and dispersing the mixture evenly to obtain a second mixed solution;
[0023] S22, slowly adding paraffin to the second mixed liquid in the presence of an antioxidant and a surfactant to react and obtain an emulsion;
[0024] S23, extruding, drying and granulating the emulsion to obtain emulsified paraffin.
[0025] The paraffin is dispersed in the polyacrylamide by means of heat capacity and emulsification dispersion, so as to reduce the problem of excessive local heating of the finally prepared energy storage material caused by the unevenness of the paraffin.
[0026] Furthermore, the low molecular weight polyacrylamide has a molecular formula of (C3H5NO) n , wherein n is the degree of polymerization, preferably 42000-71000;
[0027] Further, the antioxidant includes at least one of sodium sulfite, sodium pyrosulfite, dibutylphenol, sodium bisulfite, and sodium thiosulfate;
[0028] Furthermore, the surfactant includes a Tween surfactant. Tween surfactant is a nonionic surfactant belonging to polyoxyethylene sorbitan fatty acid ester. In the present invention, the Tween surfactant is preferably at least one of Tween20, Tween40, Tween60, Tween80 and Tween85;
[0029] Further, the paraffin wax is a mixture of hydrocarbons with carbon atoms between C18 and C30. Preferably, the straight-chain alkane content in the mixture of hydrocarbons with carbon atoms between C18 and C30 exceeds 90%, and more preferably, it is one of 52#, 54#, 56#, 58#, or any combination of two thereof.
[0030] The third object of the present invention is to provide a method for preparing an energy storage medium, comprising the following steps:
[0031] S1, adding a thickener into deionized water, stirring and swelling the water to obtain a third mixed solution;
[0032] S2, adding the composite capsule prepared by the above method into the third mixed liquid, stirring and reacting to obtain an energy storage medium.
[0033] Furthermore, in step S1, after adding deionized water into the autoclave, the system temperature is set to 60-80°C.
[0034] Furthermore, in step S1, the stirring speed during stirring is 500-1000 rpm.
[0035] Furthermore, in step S1, the time for swelling and viscosity increase is 30-60 minutes.
[0036] Furthermore, in step S2, the stirring speed is 2000-4000 rpm, and the stirring time is 30-60 min.
[0037] The fourth object of the present invention is to provide an application of the above-mentioned energy storage medium in the rapid cooling of the ground of drilling fluid. Among them, the energy storage medium needs to be pre-stirred before being used on the drilling fluid site, the stirring speed is 100-300rpm, and the stirring time is 5-20min; the energy storage medium is directly pumped into the circulating cooling pipeline at the drilling fluid site, and the circulating cooling pipeline is also connected to the condenser, and the cooling medium of the condenser is Freon. When in use, the circulating cooling pipeline contacts the outer wall of the pipeline where the drilling fluid is located for heat exchange, and the circulating cooling pipeline where the heated heat exchange medium is located is in contact with the pipeline where the energy storage medium is located. At this time, the energy storage medium and the heated heat exchange medium are continuously heat exchanged, and then the circulating cooling pipeline containing the heated heat exchange medium is heat exchanged with the condenser. After cooling, the above steps are repeated to perform a heat exchange cycle, and the microsphere core material in the energy storage medium coated with carboxymethyl chitosan restores the internal crystal state, and continues to cycle countless times to achieve the purpose of rapid cooling of the ground of drilling fluid.
[0038] Beneficial effects:
[0039] (1) The energy storage medium described in the present invention is a paraffin modified by polyacrylamide emulsification, and carboxymethyl chitosan is coated on the outside of the emulsified paraffin. The carboxymethyl and amide groups are mutually mixed to restore the internal crystal state of the microsphere core material in the energy storage medium coated with carboxymethyl chitosan. The heat exchange medium, usually water, is directly pumped into the circulating cooling pipeline at the drilling fluid site. The circulating cooling pipeline is in contact with the outer wall of the pipeline where the drilling fluid is located for heat exchange. The circulating cooling pipeline where the heated heat exchange medium is located is in contact with the pipeline where the energy storage medium is located. At this time, the energy storage medium and the heated heat exchange medium are continuously heat exchanged and cooled into the circulation through the condenser, so as to achieve the purpose of quickly reducing the temperature of the drilling fluid. Its cooling efficiency can be improved by at least 50% compared with water cooling.
[0040] (2) Using the heat capacity and emulsification dispersion method to evenly disperse the paraffin inside the polyacrylamide can effectively reduce the problem of local overheating of the energy storage material caused by uneven paraffin;
[0041] (3) The method of encapsulating carboxymethyl chitosan is used to improve the dispersion and flow of the energy storage medium in the pipeline. The system has a higher energy storage effect. DETAILED DESCRIPTION
[0042] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0043] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0044] For the purpose of this specification and the appended claims, unless otherwise stated, all numbers expressing amounts, percentages or ratios and other numerical values used in this specification and the appended claims are understood to be modified in all cases by the term "about". In addition, all ranges disclosed herein are inclusive and independently combinable.
[0045] In the experiment of the present invention, the preparation of emulsified paraffin comprises the following specific steps:
[0046] 1) Add 1000g-1500g of deionized water to a closed autoclave, raise the system temperature to 120°C-150°C, adjust the stirring speed to 1000rpm-3000rpm, slowly add 300g-500g of polyacrylamide, add it over 25min-30min, and stir and disperse it at high speed for 30min-60min;
[0047] 2) Add 30g-50g of Tween surfactant and 8g-15g of antioxidant to the above reactor in sequence, reduce the stirring speed to 100rpm-500rpm, slowly add paraffin, add it over 25min-30min, and emulsify for 60min-100min;
[0048] 3) After the reaction is completed, the mixture is transferred to an extrusion drying granulator, and the final particle size is 1.0 mm to 3.0 mm, which is emulsified paraffin.
[0049] Then, composite capsules are prepared according to the prepared emulsified paraffin, and the preparation comprises the following steps:
[0050] 1) Add 1000g-1500g of deionized water to a closed autoclave, raise the system temperature to 60°C-80°C, adjust the stirring speed to 1000rpm-3000rpm, slowly add 300g-500g of carboxymethyl chitosan, add it over 30min-60min, and stir and disperse it at high speed for 60min-90min;
[0051] 2) Add 200g to 400g of emulsified paraffin to the above reactor in batches over 20min to 30min, and continue stirring at high speed for 60min to 90min after the addition;
[0052] 3) After the reaction is completed, pour out quickly while hot, shake and sieve (20 mesh), spray the sieved material with deionized water several times until the leaching water is clear, and then transfer the collected particles into a drying oven and dry them at 60°C for 48 hours. The obtained solid particles are composite capsules.
[0053] After obtaining the composite capsule, the energy storage medium is further prepared, and the preparation method includes:
[0054] 1) Add 2000 g to 6000 g of deionized water into the autoclave and raise the system temperature to 60° C. to 80° C.;
[0055] 2) Add 30g to 40g of viscosity enhancer into the above reactor, set the stirring speed to 500rpm to 1000rpm, and allow the solution to swell and increase viscosity for 30min to 60min;
[0056] 3) Add 1500g to 5000g of the composite capsules into the above reactor, adjust the stirring speed to 2000rpm to 4000rpm, and disperse for 30min to 60min;
[0057] 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0058] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below.
[0059] Embodiment 1:
[0060] Preparation of emulsified paraffin: 1) Add 1000 g of deionized water to a closed autoclave, raise the system temperature to 120°C, adjust the stirring speed to 1000 rpm, and slowly add 300 g of polyacrylamide ((C3H5NO) 42000 ), add it within 25 minutes, and stir and disperse it at high speed for 30 minutes; 2) add 30g Tween20 and 8g sodium sulfite in the above reactor in turn, reduce the stirring speed to 100rpm, slowly add 52# paraffin wax, add it within 25 minutes, and emulsify it for 60 minutes; 3) after the reaction, transfer it to an extrusion drying granulator, and the final particle size is 1.0mm-3.0mm, which is emulsified paraffin wax.
[0061] Preparation of composite capsules: 1) Add 1000g of deionized water to a closed high-pressure reactor, raise the system temperature to 60°C, adjust the stirring speed to 1000rpm, slowly add 300g of carboxymethyl chitosan, add it over 30 minutes, and stir and disperse it at high speed for 60 minutes; 2) Add 200g of emulsified paraffin to the above reactor in batches, add it over 20 minutes, and continue to stir at high speed for 60 minutes after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48 hours, and the obtained solid particles are composite capsules.
[0062] Preparation of energy storage medium: 1) Add 2000g of deionized water into the autoclave and raise the system temperature to 60°C; 2) Add 30g of polyacrylamide (500×10 4 ), set the stirring speed to 500 rpm, and allow swelling and viscosity increasing for 30 minutes; 3) add 1500 g of composite capsules to the above reactor, adjust the stirring speed to 2000 rpm, and disperse for 30 minutes; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0063] Embodiment 2:
[0064] Preparation of emulsified paraffin: 1) Add 1100 g of deionized water to a closed autoclave, raise the system temperature to 130°C, adjust the stirring speed to 1500 rpm, and slowly add 350 g of polyacrylamide ((C3H5NO) 50000 ), add it within 30 minutes, and stir and disperse it at high speed for 40 minutes; 2) add 40g Tween40 and 10g sodium metabisulfite in the above reactor in turn, reduce the stirring speed to 200rpm, slowly add 54# paraffin wax, add it within 30 minutes, and emulsify it for 70 minutes; 3) after the reaction, transfer it to an extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is emulsified paraffin wax.
[0065] Preparation of composite capsules: 1) Add 1200g of deionized water to a closed high-pressure reactor, raise the system temperature to 70°C, adjust the stirring speed to 2000rpm, slowly add 400g of carboxymethyl chitosan, add it over 40min, and stir and disperse it at high speed for 70min; 2) Add 300g of emulsified paraffin to the above reactor in batches, add it over 30min, and continue stirring at high speed for 70min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0066] Preparation of energy storage medium: 1) Add 3000g of deionized water into the autoclave and raise the system temperature to 70°C; 2) Add 40g of polyacrylamide (800×10 4 ), set the stirring speed to 600 rpm, and allow swelling and viscosity increasing for 40 minutes; 3) add 2000 g of composite capsules to the above reactor, adjust the stirring speed to 3000 rpm, and disperse for 40 minutes; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0067] Embodiment 3:
[0068] Preparation of emulsified paraffin: 1) Add 1500g of deionized water to a closed autoclave, raise the system temperature to 140°C, adjust the stirring speed to 3000rpm, and slowly add 500g of polyacrylamide ((C3H5NO) 55000 ), add it within 30 minutes, and stir and disperse it at high speed for 50 minutes; 2) add 50g Tween60 and 12g dibutylphenol in the above reactor in turn, reduce the stirring speed to 300rpm, slowly add 56# paraffin, add it within 30 minutes, and emulsify for 80 minutes; 3) after the reaction, transfer to the extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is the emulsified paraffin.
[0069] Preparation of composite capsules: 1) Add 1500g of deionized water to a closed high-pressure reactor, raise the system temperature to 80°C, adjust the stirring speed to 3000rpm, slowly add 500g of carboxymethyl chitosan, add it within 50min, and disperse it with high-speed stirring for 80min; 2) Add 400g of emulsified paraffin to the above reactor in batches, add it within 30min, and continue to stir at high speed for 90min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0070] Preparation of energy storage medium: 1) Add 4000g of deionized water into the autoclave and raise the system temperature to 80°C; 2) Add 40g of polyacrylamide (1000×10 4 ), set the stirring speed to 700 rpm, and allow swelling and viscosity increasing for 50 minutes; 3) add 2500 g of composite capsules to the above reactor, adjust the stirring speed to 4000 rpm, and disperse for 50 minutes; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0071] Embodiment 4:
[0072] Preparation of emulsified paraffin: 1) Add 1500g of deionized water into a closed autoclave, raise the system temperature to 150°C, adjust the stirring speed to 3000rpm, and slowly add 500g of polyacrylamide ((C3H5NO) 60000 ), add it within 30 minutes, and stir and disperse it at high speed for 60 minutes; 2) add 50g Tween80 and 15g sodium bisulfite in the above reactor in turn, reduce the stirring speed to 500rpm, slowly add 58# paraffin wax, add it within 30 minutes, and emulsify it for 90 minutes; 3) after the reaction, transfer it to the extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is the emulsified paraffin wax.
[0073] Preparation of composite capsules: 1) Add 1500g of deionized water to a closed high-pressure reactor, raise the system temperature to 80°C, adjust the stirring speed to 3000rpm, slowly add 500g of carboxymethyl chitosan, add it over 60min, and disperse it with high-speed stirring for 90min; 2) Add 400g of emulsified paraffin to the above reactor in batches, add it over 30min, and continue to stir at high speed for 90min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0074] Preparation of energy storage medium: 1) Add 6000g of deionized water into the autoclave and raise the system temperature to 80°C; 2) Add 40g of polyacrylamide (800×10 4 ), set the stirring speed to 800 rpm, and allow swelling and viscosity increasing for 60 minutes; 3) add 3000 g of composite capsules to the above reactor, adjust the stirring speed to 4000 rpm, and disperse for 60 minutes; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0075] Embodiment 5:
[0076] Preparation of emulsified paraffin: 1) Add 1500g of deionized water into a closed autoclave, raise the system temperature to 150°C, adjust the stirring speed to 3000rpm, and slowly add 500g of polyacrylamide ((C3H5NO) 71000 ), add it within 30 minutes, and stir and disperse it at high speed for 60 minutes; 2) add 50g Tween85 and 15g sodium thiosulfate in the above reactor in turn, reduce the stirring speed to 500rpm, slowly add 52# paraffin wax, add it within 30 minutes, and emulsify it for 100 minutes; 3) after the reaction, transfer it to the extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is the emulsified paraffin wax.
[0077] Preparation of composite capsules: 1) Add 1500g of deionized water to a closed high-pressure reactor, raise the system temperature to 80°C, adjust the stirring speed to 3000rpm, slowly add 500g of carboxymethyl chitosan, add it over 60min, and disperse it with high-speed stirring for 90min; 2) Add 400g of emulsified paraffin to the above reactor in batches, add it over 30min, and continue to stir at high speed for 90min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0078] Preparation of energy storage medium: 1) Add 6000g of deionized water to the high-pressure reactor and raise the system temperature to 80°C; 2) Add 40g of hydroxymethyl cellulose to the above reactor, set the stirring speed to 900rpm, and swell and thicken for 60min; 3) Add 4000g of composite capsules to the above reactor, adjust the stirring speed to 4000rpm, and disperse for 60min; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0079] Embodiment 6:
[0080] Preparation of emulsified paraffin: 1) Add 1500g of deionized water into a closed autoclave, raise the system temperature to 150°C, adjust the stirring speed to 3000rpm, and slowly add 500g of polyacrylamide ((C3H5NO) 71000 ), add it within 30 minutes, and stir and disperse it at high speed for 60 minutes; 2) add 50g Tween20 and 15g sodium sulfite in the above reactor in turn, reduce the stirring speed to 500rpm, slowly add 54# paraffin wax, add it within 30 minutes, and emulsify it for 100 minutes; 3) after the reaction, transfer it to the extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is the emulsified paraffin wax.
[0081] Preparation of composite capsules: 1) Add 1500g of deionized water to a closed high-pressure reactor, raise the system temperature to 80°C, adjust the stirring speed to 3000rpm, slowly add 700g of carboxymethyl chitosan, add it over 60min, and disperse it with high-speed stirring for 90min; 2) Add 300g of emulsified paraffin to the above reactor in batches, add it over 30min, and continue to stir at high speed for 90min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0082] Preparation of energy storage medium: 1) Add 6000g of deionized water to the high-pressure reactor and raise the system temperature to 80°C; 2) Add 40g of carboxymethyl starch to the above reactor, set the stirring speed to 1000rpm, and swell and thicken for 60min; 3) Add 5000g of composite capsules to the above reactor, adjust the stirring speed to 4000rpm, and disperse for 60min; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0083] Embodiment 7:
[0084] Preparation of emulsified paraffin: 1) Add 1500g of deionized water into a closed autoclave, raise the system temperature to 150°C, adjust the stirring speed to 3000rpm, and slowly add 500g of polyacrylamide ((C3H5NO) 71000 ), add it within 30 minutes, and stir and disperse it at high speed for 60 minutes; 2) add 50g Tween40 and 15g sodium metabisulfite in the above reactor in turn, reduce the stirring speed to 500rpm, slowly add 56# paraffin wax, add it within 30 minutes, and emulsify it for 100 minutes; 3) after the reaction, transfer it to the extrusion drying granulator, and the final particle size is 1.0mm~3.0mm, which is the emulsified paraffin wax.
[0085] Preparation of composite capsules: 1) Add 1500g of deionized water to a closed high-pressure reactor, raise the system temperature to 80°C, adjust the stirring speed to 3000rpm, slowly add 500g of carboxymethyl chitosan, add it within 60min, and disperse it with high-speed stirring for 90min; 2) Add 500g of emulsified paraffin to the above reactor in batches, add it within 30min, and continue to stir at high speed for 90min after adding; 3) After the reaction is completed, pour it out quickly while hot, shake and sieve (20 mesh), spray the remaining material with deionized water several times until the leaching water is clear, then transfer the collected particles to a drying oven, dry them at 60°C for 48h, and the obtained solid particles are composite capsules.
[0086] Preparation of energy storage medium: 1) Add 6000g of deionized water to the high-pressure reactor and raise the system temperature to 80°C; 2) Add 40g of carboxymethyl starch to the above reactor, set the stirring speed to 1000rpm, and swell and thicken for 60min; 3) Add 5000g of composite capsules to the above reactor, adjust the stirring speed to 4000rpm, and disperse for 60min; 4) After the reaction is completed, the obtained suspension system is the energy storage medium.
[0087] The energy storage medium prepared by the present invention is suitable for reducing the temperature of underground drilling fluid by ground cooling method. The heat exchange medium, usually water, is directly pumped into the circulating cooling pipeline at the drilling fluid site. The circulating cooling pipeline contacts the outer wall of the pipeline where the drilling fluid is located for heat exchange. The circulating cooling pipeline where the heated heat exchange medium is located is contacted and connected with the pipeline where the energy storage medium is located. At this time, the energy storage medium and the heated heat exchange medium are continuously heat exchanged and cooled by the condenser into the circulation. The microsphere core material in the energy storage medium coated with carboxymethyl chitosan restores the internal crystal state, has higher energy storage material properties, can greatly improve the heat absorption efficiency, and achieves the purpose of rapid cooling of the drilling fluid.
[0088] Performance Testing
[0089] (1) Phase transition temperature test: The phase transition temperature of the energy storage medium prepared by the method described in Examples 1-7 was tested. The DSC curve was obtained by measuring the heating curve and the cooling curve. According to the provisions of the ICTA Standardization Committee, the DSC curve has an exothermic peak upward and an endothermic peak downward. The intersection of the front baseline extension line and the tangent line at the maximum slope of the peak front is the melting point. The crystallization peak of melting and recrystallization is taken as the characteristic peak for analysis to obtain the phase transition temperature, phase transition latent heat and other thermophysical parameters.
[0090] (2) Cooling efficiency test: The cooling pipeline used was passed with hot water (90°C, pipe diameter 10 cm, displacement 30 L / s). The hot water was used to simulate drilling fluid. At the same time, a condenser was arranged in a winding manner. The energy storage medium described in Examples 1-7 was passed into the condenser. Heat exchange was carried out between the energy storage medium and the hot water in the cooling pipeline. The temperature difference between the inlet and outlet of the pipeline was tested, and the cooling efficiency was obtained by dividing the temperature difference by the initial temperature.
[0091] Firstly, the phase change temperature and cooling efficiency of the seven embodiments were tested and compared with the conventional water cooling and air cooling effects. The results are shown in Table 1.
[0092] Table 1 Phase transition temperature and cooling efficiency of different systems
[0093] Test fluid Phase transition temperature, °C Cooling efficiency, % Example 1 16 19.9 Example 2 18 21.9 Example 3 21 25.4 Example 4 19 23.8 Example 5 15 19.6 Example 6 17 20.7 Example 7 14 18.5 Water Cooling — 12.5 Air Cooling — 6.9
[0094] From the results in Table 1, it can be seen that the conventional water cooling efficiency is 12.5%, while the air cooling efficiency is only 6.9%, both of which are no higher than 13.0%; while the phase change temperature of the energy storage medium described in the present invention is at least 14°C, the phase change temperature can reach up to 21°C, the cooling efficiency is at least 18.5%, and the maximum can reach 25.4%, which is much higher than the cooling efficiency of air cooling and water cooling.
[0095] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. An energy storage medium, characterized in that: The content of the following components is calculated by mass percentage: 33%-46% composite capsule, 0.3%-0.9% viscosity enhancer and the balance water; The composite capsule comprises an inner layer and an outer layer, the outer layer comprises carboxymethyl chitosan, and the inner layer comprises emulsified paraffin emulsified by polyacrylamide. The content of the following components is calculated by mass percentage: the composite capsule comprises 50%-70% carboxymethyl chitosan and 30%-50% emulsified paraffin.
2. The energy storage medium according to claim 1, characterized in that The viscosity enhancer includes at least one of polyacrylamide, hydroxymethyl cellulose and carboxymethyl starch; Preferably, the molecular weight of the polyacrylamide is 500×10 4 -1000×10 4 ; And / or, the etherification degree of the hydroxymethyl cellulose is 1.0; And / or, the degree of substitution of the carboxymethyl starch is 0.6; And / or, the particle size of the composite capsule is 2.0-4.0 mm, and the outer wall thickness is 1.0-2.0 mm.
3. The energy storage medium according to claim 1, characterized in that The phase change temperature of the energy storage medium is 14-21°C.
4. A method for preparing the composite capsule according to any one of claims 1 to 3, characterized in that: The following steps are involved: S11, adding carboxymethyl chitosan into deionized water and stirring to obtain a first mixed solution; S12, adding emulsified paraffin to the first mixed solution, stirring, and sieving, rinsing, and drying through shaking to obtain composite capsules.
5. The method for preparing the composite capsule according to claim 4, characterized in that: In step S11, after adding deionized water into the reactor, the temperature is 60-80°C; And / or, in step S11, the stirring speed is 1000-3000 rpm, and the stirring time is 60-90 min; And / or, in step S12, the stirring time is 60 to 90 minutes; and / or, the mesh size of the oscillation sieve is 20 mesh; And / or, the drying temperature is 60°C and the drying time is 48h.
6. The method for preparing the composite capsule according to claim 4 or 5, characterized in that: The preparation method of the emulsified paraffin comprises: S21, adding low molecular weight polyacrylamide into deionized water, stirring, and obtaining a second mixed solution; S22, adding paraffin to the second mixed liquid in the presence of an antioxidant and a surfactant to react and obtain an emulsion; S23, extruding, drying and granulating the emulsion to obtain emulsified paraffin; Preferably, the low molecular weight polyacrylamide has a molecular formula of (C3H5NO) n , where n is the degree of polymerization, ranging from 42000 to 71000; And / or, the antioxidant includes at least one of sodium sulfite, sodium pyrosulfite, dibutylphenol, sodium bisulfite, and sodium thiosulfate; And / or, the surfactant comprises a Tween surfactant; And / or, the paraffin is a mixture of hydrocarbons with carbon atoms ranging from C18 to C30.
7. A method for preparing the energy storage medium according to any one of claims 4 to 6, characterized in that: The following steps are involved: S1, adding a thickener into deionized water, stirring and swelling the water to obtain a third mixed solution; S2, adding the composite capsule into the third mixed liquid, stirring, and obtaining an energy storage medium.
8. The method for preparing the energy storage medium according to claim 7, characterized in that: In step S1, after adding deionized water into the reactor, the temperature is 60-80°C; And / or, in step S1, the stirring speed during stirring is 500-1000 rpm; And / or, in step S1, the time for swelling and viscosity increase is 30-60 minutes; And / or, in step S2, the stirring speed is 2000-4000 rpm, and the stirring time is 30-60 min.
9. Use of an energy storage medium prepared by the method of any one of claims 1 to 3 or the energy storage medium prepared by the preparation method of any one of claims 7 to 8 in rapid cooling of drilling fluid on the ground.
10. The use according to claim 9, characterized in that: The energy storage medium is pre-stirred when in use, and then directly pumped into the circulating cooling pipeline, where it is also connected to the condenser for heat exchange circulation; Preferably, the pre-stirring speed is 100-300 rpm, and the stirring time is 5-20 min; And / or, the cooling medium of the condenser is Freon.